Philippine medical thesaurus on anatomy digestive, respiratory and urogenital systems, fluids and secretions, and animal structures in Kapampangan - Carreon, Lea N. (2007)
This study entitled "Philippine Medical Thesaurus on Anatomy: Digestive, Respiratory and Urogenital Systems, Fluids and Secretions, and Animal Structures in Kapampangan" attempts to create a medical thesaurus based on the National Library of Medicines' (NLM) Medical Subject Headings (MeSH 2004). This project will benefit medical practitioners who are speakers of Kapampangan and researchers who seek information in Kapampangan. This will also promote Kapampangan as a language.